Controlling ChatGPT with Custom Instructions or API System Messages. - Rand-Hendriksen, Morten (linkedin.com, 2023)
Using ChatGPT Custom Instructions and System Messages in the OpenAI API you can provide additional context and instructions for the system to reference as you start your interaction.